Optimal use of BTK inhibitors in Waldenström’s macroglobulinemia: combination or single drug approach? - Eirini Solia; Efstathios Kastritis (Therapeutic Advances in Hematology)
Waldenström macroglobulinemia is an indolent B-cell lymphoma which although remains incurable, there are a lot of treatment options. Today, Bruton tyrosine kinase inhibitors have a central role in the management of the disease either as monotherapy or combination with other regimens, due to their efficacy, ease of administration, and safety profile. However, there is still active clinical investigation to further increase their efficacy and improve safety profile. Combinations based on BTK inhibitors may offer advantages. Second- and third-generation BTK inhibitors are also evaluated in combinations aiming to improve the depth of response, overcome genetic factors associated with poorer outcomes and reduce toxicity and duration of therapy.